Pengaruh Bauran Pemasaran dan Faktor Personal Terhadap Kepuasan Pelanggan Dengan Keputusan Pembelian sebagai Intervening - Soelama, Pricilia Christy (Universitas Sam Ratulangi, 2019)
The results of this study can be seen that the marketing mix variables significantly influence purchasing decisions. And partially the marketing mix also has a significant effect on customer satisfaction. Personal factors have a significant effect on purchasing decisions. Partially personal factors have a significant effect on Customer Satisfaction. Whereas, Purchasing Decisions have a significant effect on Customer SatisfactionKeywords: Marketing Mix, Personal Factor, Purchasing Decision, Customer Satisfaction